Histone Methyltransferases as Therapeutic Targets for Kidney Diseases - Yu, Chao; Zhuang, Shougang (Frontiers in Pharmacology, 2019)
Emerging evidence has demonstrated that epigenetic regulation plays a vital role in gene expression under normal and pathological conditions. Alterations in the expression of histone methyltransferases have been reported to be associated with multiple kidney diseases, including acute kidney injury, chronic kidney disease, diabetic Nephropathy, polycystic kidney disease, and renal cell carcinoma. In this review, we summarize recent knowledge of expression and activation of various histone methyltransferases and their functional roles in kidney diseases. We also provide new insights into the pathogenesis of epigenetic regulation involved in the development of kidney diseases.